All-PP composites (PURE®) with unidirectional and cross-ply lay-ups: dynamic mechanical thermal analysis (eXPRESS Polymer Letters)
All polypropylene (all-PP) composite laminates with unidirectional (UD) and cross-ply (CP) lay-ups were produced by hot consolidation from oriented coextruded PP tapes (PURE®). The consolidation of the tapes, wound on a steel plate, occurred in autoclave vacuum bag molding. The set processing conditions resulted in all-PP laminates of high rigidity as the PP copolymer surface layers of the tapes were molten and thus forming the matrix, while their PP homopolymer core remained unaffected and thus fulfilled its role as reinforcement. Specimens cut off from the laminates were subjected to dynamic mechanical thermal analysis (DMTA) in a broad temperature range (T = –50…120°C) at various frequencies (f = 10–2…101). For the DMTA results the time-temperature superposition principle was adopted and master curves in the form of storage modulus vs. frequency (f = 10–9…1020) and loss factor vs. frequency were created.